The Internet’s effect on libraries : some personal observations - Chen, Ya-ning (2021)
A library’s collection development is a continuous process and responds to the needs and goals of its users. It includes not just the policy of collection development itself but also the procedures of selection, acquisition and evaluation. With the use of the Internet and the advent of the virtual library, the new direction in collection development has become a number one issue. This article considers future directions for collection development from four standpoints: changes under the virtual library environment; the means of acquisition; related problems; and future directions.